Accuracy of quantitative magnetic resonance imaging in the detection of ex vivo focal cartilage defects. Issue 8 (7th January 2005) - Graichen, H; Al-Shamari, D; Hinterwimmer, S; von Eisenhart-Rothe, R; Vogl, T; Eckstein, F
Abstract : Background: No established, non-invasive diagnostic procedure for quantifying focal cartilage defects is currently available. Objective: To test the accuracy of quantitative magnetic resonance imaging (qMRI) for reliable determination of cartilage defect size in various compartments of the human knee. Methods: 24 tibial and patellar cartilage plates were harvested during knee arthroplasty. 74 cylindrical defects with diameters of 3, 5, and 8 mm were created with a punch. In 15 specimens (51 defects), the cartilage cylinders (inside the punch) were removed (approach 1), while in 9 specimens (23 defects) the surrounding tissue was removed mechanically and the cartilage cylinder was left in place (approach 2). All plates were imaged with a T1 weighted water excitation gradient echo sequence at a resolution of 1.5 mm×0.31 mm×0.31 mm. The defect size was computed from the image data after interactive segmentation and compared with the known dimensions of the cylinders. Results: Although there was a significant overestimation of the defect size by qMRI in 3 mm defects (mean (SD) +1.3 (0.58) mm = ±42%; p<0.001), the overestimation was only +1.0 (0.57) mm (±21%; p<0.05) in 5 mm defects and +0.1 (0.39) mm (±4%; p = 0.31) in 8 mm defects (approach 1). Values were similar for approaches 1 and 2 and for patellar and tibial cartilage plates. Conclusions: These findings show that qMRI allows accurate quantification of focal cartilage defects. It may therefore represent a valuable tool in the diagnosis of traumatic cartilage lesions, osteochondrosis dissecans, and osteochondral fractures, and in monitoring their responsiveness to surgical or other treatments.